The Roles of Oxide Growth and Sub-Surface Facets in Oxygen Evolution Activity of Iridium and Its Impact on Electrolysis. Issue 15 (20th November 2019) - Alia, Shaun M.; Ha, Mai-Anh; Anderson, Grace C.; Ngo, Chilan; Pylypenko, Svitlana; Larsen, Ross E.
Abstract : This paper combines density functional theory calculations and electrochemical testing to study activity differences among iridium (Ir) surfaces in the oxygen evolution reaction. Ir metal/hydroxide is significantly more active than Ir oxide, which may be due to oxide skins at the surface weakening O-binding relative to pure metal or oxide surfaces. Here we report a disparity in activity between Ir and Ir oxide in half-cells not observed in single-cells. Extended operation at elevated temperature and potential were found to result in oxide growth, limiting how surface differences affect electrolyzer performance. Comparisons of half- and single-cell testing were used to assess how well rotating disk electrode testing predicts membrane electrode assembly performance and durability. Although oxygen evolution activities in half-cells can translate to single-cells, standard rotating disk electrode test procedures can exaggerate the activity benefit of a metal/hydroxide surface relative to membrane electrode assembly performance under typical operating conditions; it also appears that a half-cell test cannot reasonably accelerate activity loss from continual operation. While a variety of novel catalyst approaches, including alloying, faceting, morphology, and supports can improve oxygen evolution kinetics, these results suggest that Ir surfaces at different oxide states may struggle to improve performance at the device level.